Storytelling and social media as tools for brand recognition: The role of digital influencers - Peixe, Catarina Castedo Rodrigues (2022)
This dissertation’s main goal was to understand the effect storytelling and influencer marketing have on the consumers’ purchase intention, in a time when the connection between consumer and brand is extremely relevant. In recent times the internet came to change the way communication happens, these changes affected the advertising sector as much as any other. Giving the amount of information available online, the consumers’ profile changed too. People are searching for personalized information and brands that match their personal values. By using a quantitative methodology, surveys, this dissertation intends to evaluate Portuguese’s’ presence online as well as the ways in which they are affected by storytelling and influencer marketing. As a main conclusion it was possible to assess that Portuguese are affected by these marketing strategies, however, not in an evenly way. Age turned out to be an important factor to take in consideration.